The Red Coast : Radicalism and Anti-Radicalism in Southwest Washington - Goings, Aaron; Snider, Roger F.; Barnes, Brian L., 1979- (Book collections on Project MUSE., 2019)
"The Red Coast is a lively and readable informal history of the labor, left-wing, and progressive activists who lived, worked, and organized in southwest Washington State from the late nineteenth century until World War II. The book serves as a hidden history for a region frequently identified with conservatism, rescuing these working-class activists from obscurity and placing them at the center of southwest Washington's history."--Back cover